The Impact of Painting on Students’ Creative Development and Visual Thinking - Sohibova Zuhroxon Akmal qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores the impact of painting on students’ creative development and visual thinking in higher education. It examines how pedagogical approaches, project-based learning, and interactive methods contribute to enhancing students’ artistic expression, aesthetic perception, and problem-solving skills. The study highlights the importance of both individual and collaborative painting activities for holistic student development.